The Influence Of Service Quality And Tourism Facilities On Visitor Satisfaction - Aprilia, Erica; Mursidi; Robbie, R.Iqbal (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research was conducted with the aim of determining the effect of service quality and tourist facilities on visitor satisfaction. The sample used in this research was visitors who came to the Sengkaling Recreation Park. This sampling technique was carried out using a questionnaire, the number of samples used in this research was 100 respondents with a purposive sampling method and SLOVIN formula. The data analysis method uses scale range analysis and data processing uses SPSS version 25. The results of this study are Service quality variables have a positive and significant effect on visitor satisfaction, Tourist facilities do not have a significant effect on visitor satisfaction, Service quality and tourism facilities simultaneously have a significant effect on visitor satisfaction.